Detection of Bacterial Wilt Pathogen and Isolation of Its Bacteriophage from Banana in Lumajang Area, Indonesia - Hardian Susilo Addy; Norita Fatatik Azizi; Paniman Ashna Mihardjo (International Journal of Agronomy)
Bacterial wilt disease on banana is an important disease in Lumajang District and causes severe yield loss. Utilizing bacteriophage as natural enemy of pathogenic bacteria has been widely known as one of the control strategies. This research was aimed at determining the causing agent of bacterial wilt on banana isolated from Lumajang area, to obtain wide-host range bacteriophages against bacterial wilt pathogen and to know the basic characteristic of bacteriophages, particularly its nucleic acid type. Causative agent of bacterial wilt was isolated from symptomatic banana trees from seven districts in Lumajang area on determinative CPG plates followed by rapid detection by PCR technique using specific pair-primer. Bacteriophages were also isolated from soil of infected banana crop in Sukodono District. Morphological observation showed that all bacterial isolates have similar characteristic as common bacterial wilt pathogen, Ralstonia solanacearum. In addition, detection of FliC region in all isolates confirmed that all isolates were R. solanacearum according to the presence of 400 bp of FliC DNA fragment. Moreover, two bacteriophages were obtained from this experiment (ϕRSSKD1 and ϕRSSKD2), which were able to infect all nine R. solanacearum isolates. Nucleic acid analysis showed that the nucleic acid of bacteriophages was DNA (deoxyribonucleic acid).